Informal Financial Institutions (IFIs) and Poverty Reduction in Konshisha Local Government Area of Benue State, Nigeria - C. T, Beeior; S.O, Ajegi; J. A, Tyoakosu (Asian Journal of Social Sciences and Management Studies, 2016)
This study was carried out to examine the impact of informal financial institutions (IFIs) on poverty reduction in Konshisha local government area of Benue State, Nigeria. A total of 220 questionnaires were administered to households in the study area; 110 each for beneficiaries and non-beneficiaries of informal financial institutions (IFIs) in the study area. Data collected were analyzed using P-Apha, logit regression model, simple percentages and T-test statistics. The result showed that the incidences of poverty (po), depth (P1) and severity (P2) were found to be worse among the non-beneficiaries of IFIs. The result of T-test of difference in mean of real household consumption-Expenditure of beneficiaries & non- beneficiaries of IFIs also indicated clearly that beneficiaries of IFIs have more real household consumption expenditure than non-beneficiaries of IFIs in the study area. The result of the Logit regression model showed that out of the seven variables regressed, only three namely: averages monthly savings, education & household size have influenced significantly the poverty status of the respondents at 5% level. The study identified shortage of funds for disbursement to members as the major problem hindering the smooth operation of IFIs in the study area. It was suggested among other recommendations that government and other relevant organizations should provide soft loans to members of IFIs through the IFIs in which they belong to expand their small businesses and hence reduce their poverty level.